Embracing the other : addressing xenophobia in the new literatures in English - Mohr, Dunja M., 1968- (Rodopi, 2008)
In the wake of addressing multiculturalism, transculturalism, racism, and ethnicity, the issue of xenophobia and xenophilia has been somewhat marginalized. The present collection seeks, from a variety of angles, to investigate the relations between Self and Other in the New Literatures in English. How do we register differences and what does an embrace signify for both Self and Other? The contributors deal with a variety of topics, ranging from theoretical reflections on xenophobia, its exploration in terms of intertextuality and New Zealand/Maori historiography, to analyses of migrant and border narratives, and issues of transitionality, authenticity, and racism in Canada and South Africa. Others negotiate identity and alterity in Nigerian, Malaysian, Australian, Indian, Canadian, and Caribbean texts, or reflect on diaspora and orientalism in Australian¿Asian and West Indian contexts.
Keywords: Commonwealth literature (English) -- History and criticism.; Cultural pluralism in literature.; Racism in literature.; Xenophobia.; Littérature du Commonwealth (anglaise) -- Histoire et critique.; Diversité culturelle dans la littérature.; Racisme dans la littérature.; Xénophobie.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; Commonwealth literature (English); Cultural pluralism in literature; Racism in literature; Xenophobia; Criticism, interpretation, etc.